International Challenges in Investment Arbitration - Akbaba, Mesut; Capurro, Giancarlo; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
As the proverbial workhorse of international economic law, investment arbitration is heavily relied upon around the globe. It has to cope with the demands of increasingly complex proceedings. At the same time, investment arbitration has come under close public scrutiny in the midst of heated political debate. Both of these factors have led to the field of investment protection being subject to continuous changes. Therefore, it presents an abundance of challenges in its interpretation and application. While these challenges are often deeply rooted in the doctrinal foundations of international law, they similarly surface during live arbitral proceedings. International Challenges in Investment Arbitration serves not only as a collection of recently debated issues in investment law; it also deals with the underlying fundamental questions at the intersection of investment arbitration and international law. The book is the product of the 1st Bucerius Law Journal Conference on International Investment Law & Arbitration. It combines the current state of knowledge, new perspectives on the topic as well as practical issues and will be of interest to researchers, academics and practitioners in the fields of international investment law, international economic law, regulation and comparative law.
TABLE OF CONTENTS -- Preface by the Editors -- List of Contributors -- Part I: The State in International and Investment Law -- Chapter 1: -- Rethinking the Relevance of Customary International Law to Issues of Nationality in Investment Treaty Arbitration (Javier Garca Olmedo) -- Chapter 2: --Investment Claims and Annexation of Territory: Where General International Law and Investment Law Collide (Sebastian Wuschka) -- Chapter 3: -- General Exception Clauses in International Investment Agreements: A Case for Systemic Integration? (Tobias Ackermann) -- Chapter 4: -- International Norms, a Defense in Investment Treaty Arbitration? (Dafina Atanasova) -- Chapter 5: -- Towards a New Regulatory Paradigm under Recent FTA Investment Chapters? (Elsa Sardinha) -- Part II: Investment Arbitration and the European Legal Order -- Chapter 1: -- A Comparative Law Approach as a Technique for Solving Conflicts between EU law and Investment Arbitration: The Case of the ECtHR. -- (Blerina Xheraj) -- Chapter 2: -- The Energy Charter Treaty and European Union Law: Mutually Supportive Instruments for Economic Cooperation or Schizophrenia in the Acquis? (Cees Verburg) -- Chapter 3: -- The Structural Need for Intra-EU BIT Protection (Emily Sipiorski) -- Chapter 4: -- Is One Permanent Instance Enough? A Comparison Between the WTO Appellate Body and the Proposed Investment Court System (Marcus Weiler) -- Part III: Practical Issues in Investor State Proceedings -- Chapter 1: -- The Appropriate Use of Bifurcation as a Means for Increasing Efficiency in Investment Arbitration (Jola Gjuzi) -- Chapter 2: -- Effective Management of Mass Claims Arbitration What Could Be Learnt from International Tribunals? (Katarzyna Szczudlik) -- Chapter 3: -- The Impact of the Economic and Political Situation Prevailing in the Host State on Compensation under International Investment Law (Sven Lange) -- Chapter 4: -- The Impact of Third Party Funding on an ICSID Tribunals Decision on Security for Costs (Alexander Hoffmann) -- Concluding Remarks -- Rationalising Costs in International Arbitration: A Tall Order? (Speech by Neil Kaplan QC CBE SBS) -- Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: International commercial arbitration -- Congresses; Investments, Foreign (International law) -- Congresses; International commercial arbitration; Investments, Foreign (International law); LAW / Arbitration, Negotiation, Mediation; BUSINESS & ECONOMICS / International / Economics; Arbitration; Comparative Law; EU Law; Foreign Investment Arbitration; International Investment Law; International Trade & Economic Law; Investment Law; Investment Treaties; Mass Claims Arbitration; Regulation; Electronic books